Periprotetické infekce megaprotéz po resekcích kostních nádorů oblasti kolene - Včelák, Josef; Matějovský, Zdeněk; Kofránek, Ivo; Kubeš, Radovan; Lesenský, Jan (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF THE STUDY The study presents the monocentric retrospective study of a group of patients with malignant tumours around the knee, treated by a wide resection and a reconstruction with megaprosthesis due to infectious complications. Provided is a detailed analysis of each operative treatment due to the manifestation and process of periprostethic infection of the knee megaprosthesis and the use of external fixator during a two-stage revision. MATERIAL AND METHODS Between 01/1993 and 12/2013, a total of 67 cemented megaprostheses were assessed, with a detailed analysis of 12 patients with periprosthetic infection. The Kaplan-Meier method and MSTS for lower extremity clinical assessment were used and a range of motion was evaluated. RESULTS The endoprosthesis failed due to all kinds of complications (mechanical, biological, infection) in 27 (40.3%) patients. The estimated one-year survival rate from the surgery was 94%, the five-year survival rate was 72%, and the ten-year survival rate was 46%. Based on the statistical analysis of the implant survival due to infection, the one-year survival rate was 94%, the five-year survival rate was 75%, and the ten-year survival rate was 57%. Three patients were treated with radical surgical debridement. Five patients were treated with a two-stage revision with a cement spacer and external fixator, and three patients underwent nail fixation. Clinical values before and two years after the revision surgery for periprosthetic infection using MSTS were assessed. The mean of the difference of clinical values was 1.91 and the p value of paired t-test was 0.24, therefore there was no prove of the clinical result difference using MSTS before and after the revision surgery. DISCUSSION The acute radical debridement and lavage is preferred, if the surgery can be done up to three weeks after the first clinical signs of infection under the condition of good retention of the implant. In case of extensive infectious damage, when abscess, fistula and loosening of the implant are present and when the patient has a good oncological prognosis, we prefer a twostage revision with a cement spacer stabilized by an external fixator. In patients with mitigated infection or uncertain oncological prognosis we prefer a two-stage revision with the combination of a cement spacer and intramedullary nail fixation. CONCLUSIONS The study presents the results of operative treatment of periprosthetic infection of megaprosthesis and the modification of the two-stage replantation of infected MP with the use of external fixation for stabilisation of a non-articulated cement spacer allowing the patient to remain active during the time before the second stage. Key words: periprosthetic infection, megaprosthesis, bone tumour, external fixator, two-stage revision.
Keywords: Fracture Fixation, Internal; Bone Neoplasms; Knee Joint; lidé; Survival Analysis; Knee Prosthesis; nádory kostí; Reoperation; reoperace; debridement; protézy kolene; retrospektivní studie; selhání protézy; Debridement; analýza přežití; vnitřní fixace fraktury; Arthroplasty, Replacement, Knee; kolenní kloub; Retrospective Studies; Prosthesis Failure; totální endoprotéza kolene; Humans